DAMPAK PELATIHAN PEMANFAATAN APLIKASI INSTAGRAM DALAM MENINGKATKAN PEROLEHAN LABA PERUSAHAAN UMKM - Untari, Febriani Nur (IKIP Siliwangi, 2020)
AbstractÂ This research is motivated by the gap between the latest technology and the unpreparedness of business people to utilize the technology. This study uses the theory of training, the concept of profit, and the concept of social media Instagram. The method used is a descriptive method with a qualitative approach. Data obtained through the process of interviews, observation and study of documentation. As for the population in this study were micro and small and medium entrepreneurs in the field of fashion and the sample was the Cimahi City UMKM Acceleration participants totaling 10 people consisting of 2 men and 8 women. The results showed that there was an increase in company profitability after the implementation of Instagram social media training.AbstractÂ This research is motivated by the gap between the latest technology and the unpreparedness of business people to utilize the technology. This study uses the theory of training, the concept of profit, and the concept of social media Instagram. The method used is a descriptive method with a qualitative approach. Data obtained through the process of interviews, observation and study of documentation. As for the population in this study were micro and small and medium entrepreneurs in the field of fashion and the sample was the Cimahi City UMKM Acceleration participants totaling 10 people consisting of 2 men and 8 women. The results showed that there was an increase in company profitability after the implementation of Instagram social media training.Â Penelitian ini dilatarbelakangi oleh adanya kesenjangan antara teknologi yang mutakhir dengan ketidaksiapan para pelaku usaha untuk memanfaatkan teknologi tersebut. Penelitian ini menggunkan teori pelatihan, konsep laba, dan konsep media sosial instagram. Metode yang digunakan adalah metode deskriptif dengan pendekatan kualitaaif. Data yang diperoleh melalui proses wawancara, observasi dan studi dokumentasi. Adapun yang menjadi populasi dalam penelitian ini adalah para pelaku usaha mikro kecil dan menengah di bidang mode dan yang menjadi sample adalah peserta Akselerasi UMKM Kota Cimahi yang berjumlah 10 orang yang terdiri dari 2orang laki-laki dan 8 orang perempuan. Hasil penelitian menunjukan bahwa adanya peningkatan perolehan laba perusahaan setelah terlaksananya pelatihan pemanfaatan media sosial Instagram.